Anatomical Variation of Olfactory Fossa on Computed Tomography of Paranasal Sinuses - Shahid, Madeeha; Mahmood, Rashid; Ullah, Hidayat; Sheraz, Muhammad Atif; Ibrahim, Muhammad Imran; Ali, Farzana Zulfiqar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of anatomical variation of olfactory fossa among the adult Pakistani population by Keros classification on computed tomography (CT) of paranasal sinuses. Study Design: Cross-sectional study Place and Duration of Study: Department of Radiology, Combined Military Hospital, Rawalpindi Pakistan, from May 2019 to Mar 2020. Methodology: A total of 65 patients of either gender were included. Patients with previous trauma or surgery of the skull base or paranasal sinuses, malignant diseases of the sinuses and congenital anomalies were excluded. All the included patients in the study underwent CT paranasal sinuses. Measurements of the olfactory fossae followed by grouping as per Kero’s classification were done, and CT findings were recorded. Results: The patients included in the study ranged from 18 to 65 years, with a mean age of 33.09±10.86 years and 72.3% of patients 18 to 40 years of age. Of 65 patients, 36(55.4%) were males, and 29(44.6%) were females. The mean CT depth of the olfactory fossa was 6.34 ±4.03mm. Type-I olfactory fossa by Keros classification was found in 17(26.2%), Type-II in 35(53.8%) and Type-III in 13(20%) of patients. Conclusion: This study concluded that Keros Type-II is the most common anatomical variation of olfactory fossa among the adult Pakistani population on CT of paranasal sinuses with an intermsediate risk of intracranial complications during endoscopic sinus surgery involving this region.